2020
DOI: 10.3390/cells9092037
|View full text |Cite
|
Sign up to set email alerts
|

Gateways for Glutamate Neuroprotection in Parkinson’s Disease (PD): Essential Role of EAAT3 and NCX1 Revealed in an In Vitro Model of PD

Abstract: Increasing evidence suggests that metabolic alterations may be etiologically linked to neurodegenerative disorders such as Parkinson’s disease (PD) and in particular empathizes the possibility of targeting mitochondrial dysfunctions to improve PD progression. Under different pathological conditions (i.e., cardiac and neuronal ischemia/reperfusion injury), we showed that supplementation of energetic substrates like glutamate exerts a protective role by preserving mitochondrial functions and enhancing ATP synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 111 publications
0
13
0
Order By: Relevance
“…We recently reported that in different neuropathological settings, including AD, mitochondrial functions could be retained by supplying alternative substrates (e.g., glutamate) [15,40]. Glutamate could be used by neuronal cells to compensate for energy deficits and, at the same time, to scavenge for ROS, thus improving mitochondrial performance by acting at different sites [15,40].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently reported that in different neuropathological settings, including AD, mitochondrial functions could be retained by supplying alternative substrates (e.g., glutamate) [15,40]. Glutamate could be used by neuronal cells to compensate for energy deficits and, at the same time, to scavenge for ROS, thus improving mitochondrial performance by acting at different sites [15,40].…”
Section: Discussionmentioning
confidence: 99%
“…Both SH-SY5Y and rat primary cortical neurons were plated on 12-well plates, and at the end of the experimental procedure, the cells were incubated with 0.5 mL of MTT solution (0.5 mg/mL in PBS) in the dark at 37 • C and a 5% CO 2 atmosphere in a humidified incubator. After 1 h, the cells were washed with PBS, and the produced formazan crystals were dissolved in 0.5 mL of DMSO [15,40]. A decrease in mitochondrial activity resulted in a reduction in the amount of formazan produced and therefore in the absorbance value.…”
Section: Cell Viability Assaymentioning
confidence: 99%
See 3 more Smart Citations